The Silk Road: Integration and Self-Structuring of Transregional Spaces - Alla B. Carimova (Сравнительная политика)
In international relations integration processes and mechanisms are closely related to multilateral order of interactions among actors. Observations over integration activity of non-regional actors in former Soviet area reveals the battle of geopolitical interests being held during already several centuries.The author believes that EU and US integration activities in Eurasia as well as activities of multilateral institutions under their control are run in quite competitive conditions seen through not only the quantity and volume of investments but also via autonomous ways of their implementation.